1989
DOI: 10.1152/ajpendo.1989.256.2.e295
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and responsiveness during lactation and dry period in goats

Abstract: To investigate the role of insulin in partitioning nutrients between the mammary gland and other tissues during lactation in ruminants, euglycemic-hyperinsulinemic clamps were performed in goats during early lactation (15-26 days postpartum), midlactation (78-91 days postpartum), and dry period (169-194 days postpartum). Insulin was infused at 0.4, 0.7, 1.9, 4.4, and 10 micrograms/min. Basal plasma glucose was constant during all periods despite the fact that basal glucose utilization was approximately 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 31 publications
5
64
2
1
Order By: Relevance
“…Endogenous glucose production was suppressed by 30 to 60% and glucose utilization was stimulated by 0 to 30% when plasma insulin concentration was increased to twofold that of basal states by insulin infusion with a maintained plasma glucose concentration [29][30][31]. This suggests that the increase in plasma insulin concentration during the postfeeding period in the present study should produce a decrease in glucose entry and no change or a slight increase in glucose utilization.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Endogenous glucose production was suppressed by 30 to 60% and glucose utilization was stimulated by 0 to 30% when plasma insulin concentration was increased to twofold that of basal states by insulin infusion with a maintained plasma glucose concentration [29][30][31]. This suggests that the increase in plasma insulin concentration during the postfeeding period in the present study should produce a decrease in glucose entry and no change or a slight increase in glucose utilization.…”
Section: Discussionmentioning
confidence: 49%
“…A catheter for blood sampling was inserted into the skin loop of the carotid artery at 2 h before the experiments, and was flushed and filled with a sterile solution of trisodium citrate (38 g·L −1 ). Blood samples (5 mL) for glucose and insulin determinations were obtained from the arterial catheter immediately before (0 min) and at 5,10,15,30,45,60,90, 120 and 180 min after feeding. Additional blood samples (5 mL) were taken for VFA determination at 0, 30, 60, 90, 120 and 180 min after feeding.…”
Section: Blood Metabolites and Insulin And Ruminal Characteristicsmentioning
confidence: 99%
“…23) Glucose transport, which is the first step in glucose utilization, has been found to be a rate-limiting step in glucose metabolism in ruminants as in non-ruminants, and to be regulated by insulin. 24,25) Glucose transport across the plasma membrane is carried out by five facilitative glucose transporter proteins in both monogastrics and ruminants: the insulin-sensitive (GLUT-4), which are mainly expressed in adipose tissue and skeletal muscles, and the noninsulin sensitive glucose transporters (GLUT-1, 2, 3, 5). 26) Insulin resistance in T2D is manifested by decreased insulin stimulated glucose transport and metabolism in adipocytes and skeletal muscle resulting in down-regulation of the major insulin-responsive glucose transporter, GLUT-4.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have shown that lactation in goats is associated with an impairment in the ability of insulin to maximally stimulate glucose utilisation [28]. This insulin resistance in goats originates from a postreceptor defect [10].…”
Section: Lactationmentioning
confidence: 99%